Comparative Microbial Nitrogen Functional Gene Abundances in the Topsoil vs. Subsoil of Three Grassland Habitats in Northern China - Liu, Yuqing; Chi, Qiaodong; Cheng, Hui; Ding, Huanxin; Wen, Teng; Zhao, Jun; Feng, Xiaojuan; Zhang, Jinbo; Cai, Zucong; Liu, Guohua (Frontiers in Plant Science, 2022)
The microbial groups of nitrogen fixers, ammonia oxidizers, and denitrifiers play vital roles in driving the nitrogen cycle in grassland ecosystems. However, the understanding of the abundance and distribution of these functional microorganisms as well as their driving factors were limited mainly to topsoil. In this study, the abundances of nitrogen functional genes (NFGs) involved in nitrogen fixation (nifH), ammonia oxidation (amoA), and denitrification (nirK, nirS, and nosZ) were investigated in both topsoil (0–10 cm, soil layer with concentrated root) and subsoil (30–40 cm, soil layer with spare root) of three grassland habitats in northern China. The abundance of NFGs decreased with soil depth except for the archaeal amoA gene and the distribution of nifH, archaeal amoA, nirK, and nirS gene was significantly impacted by grassland habitats. Moreover, the distribution of NFGs was more responsive to the vertical difference than horizontal spatial heterogeneity. Redundancy analysis revealed that the distribution pattern of overall NFGs was regulated by grassland habitats, and these regulations were more obvious in the subsoil than in the topsoil. Variance partitioning analysis further indicated that soil resource supply (e.g., organic matter) may control the vertical distribution of NFGs. Taken together, the findings in this study could fundamentally improve our understanding of the distribution of N cycling-associated microorganisms across a vertical scale, which would be useful for predicting the soil N availability and guiding the soil N management in grassland ecosystems.